A multifaceted analysis of pesticide utilization in market gardening along the Ruzizi plain: Exploring factors, farmer perceptions & media influence - Angel Anthony Kasonta; Thakur, Sugandha Shekhar; Jean-Claude Masumbuko Birindwa (Plant Science Today, 2024)
Along the Ruzizi plain, subsistence agriculture constitutes households' primary food source. Regardless of the environment, the low level of pesticide use ensures less effective disease and pest control. This is why a study was carried out in the Ruzizi plain to identify the main determinants of pesticide use on vegetable crops for effective control of diseases and pests that significantly reduce the yield of these crops, which play an economically important role for producers and the role of the media in this context. The data was collected using a closed-type survey questionnaire on 90 market gardeners distributed equally between localities applying the probit model. The results of the probit model estimation reveal that about nine factors positively influence the use of pesticides: membership in a cooperative (p=0.0012), access to agricultural credit (p=0.0153), experience in agriculture (p=0.0008), experience in market gardening (p=0.0197), standard of living (p=0.0139), yield (p=0.0001), capacity building (p=0.0035), the area exploited (p=0.0011) and the cultivation system (p=0.0233). In addition, tomatoes are the leading vegetable crop grown by many market gardeners (61.1%), followed by amaranth (20%) and onions (18.9%). Also, 67.8% of market gardeners use pesticides compared to 32.2% who do not use them. Thus, considering these factors would contribute to decision-making when carrying out certain activities to improve market gardening, contributing considerably to the fight against food insecurity. Also, it is advised that the media work harder to inform rural residents and areas about the agenda for rural development.